Thai Families engaged in Culturally based Traditional Learning in Southern - Khajornchaikul, Piyathida (Mahachula Academic Journal, 2025)
The purpose of this research was to study Thai families engaged in Culturally based traditional learning in southern Thailand. A quantitative research design, 299 A self – administered questionnaire was used to collect data from families in areas where the Community Family Development Center was active. These areas had activities or family – related project that met at least one of the three indicators of the Worm families’ concepts: family relationship, family role and self-sufficiency of family. The study also included components related to practice, application cultural for dairy life, and sustainability of traditional culture with in the community. Descriptive statistics were used for data analysis. The research finding reveled that, in term of the role and practicing traditional were found to be the same level. The most prominent aspect was the role of caring for adolescence 89.6%, and followed by caring for child aged over 6 – 13 years old 87.6%. Regarding the application of cultural practice in dairy life for children was teaching for think well, making wishes, do good deeds, and fostering moral behavior 59.9%. Finally, for cultural sustainable in community 28.1% of families encouraged community members to participate in cultural and traditional activities. The study suggests that local governments and families should collaborate to promote culture and traditional activities, therefor strengthening relationships and preventing family related problems.